Methodological approaches to structural-logical analysis of interaction for business cycles - Safiullin, Marat R.; Leonid A. Elshin, Aliya A. Abdukaeva, (Opción, 2019)
The aim of the study is to investigate methodological approaches to the structural-logical analysis of interaction for business cycles via the use of complex multidimensional methods for constructing differential equations of production functions. As a result, the sentiments of economic agents under the influence of short-term positive impulses in capital markets begin to gain momentum and the expectations of economic agents launch mechanisms for reviving macroeconomic generations in the short-term cycle. In conclusion, the solution of the set task allows us to determine and empirically justify the logic of phase shifts in the cyclical development of the economy.